Bone Density Evaluation In Vivo after Installation of Implants Using an Osteotome Technique: Case Report - Santagata, Mario; Rienzo, Domenico; d’Amato, Salvatore; Tartaro, Gianpaolo; Tozzi, Umberto (The Journal of Dentists, 2015)
The aim of our study was to evaluate bone density before and after implant placement by the osteotome technique in vivo and human posterior maxilla. Patient treated with implants placement in position of right upper canine and right first upper premolar by osteotome technique. Radiological evaluation by CBCT was performed before and 4 months after surgery. The results showed that osteotome technique achieved a significant increase in bone density in area of right upper canine but there was not increase in area right first upper premolar. According to our results, the osteotome technique is the best choice for implant placement in posterior maxilla but only when a low bone density is present.